2014
DOI: 10.1117/1.jbo.19.10.105006
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced retinal damage threshold for repetitive-pulse exposure to 100-μs pulses

Abstract: The laser-induced retinal injury thresholds for repetitive-pulse exposures to 100-μs-duration pulses at a wavelength of 532 nm have been determined for exposures of up to 1000 pulses in an in vivo model. The ED50 was measured for pulse repetition frequencies of 50 and 1000 Hz. Exposures to collimated beams producing a minimal retinal beam spot and to divergent beams producing a 100-μm-diameter retinal beam spot were considered. The ED50 for a 100-μs exposure was measured to be 12.8 μJ total intraocular energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Melanin-containing organelles known as melanosomes are the main absorbing particles found in the monolayer of cells of the retinal pigment epithelium (RPE) layer of the retina [25,26]. The formation of small bubbles (microcavitation) is the primary retinal damage mechanism for laser pulses in the 10 −9 to 10 −6 seconds range around the melanosomes in the RPE cells [27,28]. The formation of cavitation bubbles are highly correlated to cell death, and it is critical to understand the relationship between laser irradiance and damage.…”
Section: Resultsmentioning
confidence: 99%
“…Melanin-containing organelles known as melanosomes are the main absorbing particles found in the monolayer of cells of the retinal pigment epithelium (RPE) layer of the retina [25,26]. The formation of small bubbles (microcavitation) is the primary retinal damage mechanism for laser pulses in the 10 −9 to 10 −6 seconds range around the melanosomes in the RPE cells [27,28]. The formation of cavitation bubbles are highly correlated to cell death, and it is critical to understand the relationship between laser irradiance and damage.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that also for the human eye a diffraction limited focus can be achieved [29, 30]. In another study which was done by Lund et al in 2008 [31] measurements on non‐human primates were performed by using wavefront‐corrected beams to reduce refractive errors and aberrations. Though the results show lower thresholds than without using wavefront correction the retinal spot size could not be determined.…”
Section: Wave Optical Phenomena In the Field Of Eye Safetymentioning
confidence: 99%
“…In studies of multiple-pulse exposures in the eye, it is common to present the energy threshold per pulse as a function of the number of pulses in the train. 23,[30][31][32] This approach is useful for visualizing the cumulative effect of pulses but assumes pulses of equal length and pulse trains with a consistent PRF. These parameters are more diverse in our study given that we held TOT constant and varied the pulse duration and PRF to fit the specified duty cycle and number of pulses.…”
Section: Number Of Pulsesmentioning
confidence: 99%
“…There has been extensive research into multiple-pulse MVL thresholds in the eye using number of pulses and pulse repetition frequency (PRF) as variables, for the infrared [23][24][25][26] and visible [27][28][29][30][31] wavelength regions. Clark et al 32 provided a theoretical analysis of multiple-pulse thermal damage thresholds to the retina based on the Arrhenius integral model, for both visible and NIR wavelengths.…”
Section: Introductionmentioning
confidence: 99%